Stress hyperglycemia: clinical profile and outcome in critically ill children - Grace R., Diana; V., Poovazhagi (International Journal of Contemporary Pediatrics, 2017)
Background: Stress hyperglycemia (SH) occurs commonly during critical illness in children with previously normal glucose homeostasis. Objective of present study was to study the clinical presentation, underlying illness and the outcome of stress hyperglycemia among critically ill children. Methods:Children attending the outpatient department and the casualty were admitted to Emergency department based on the triage guidelines. Children with blood glucose above 200 mg/dl on admission to the emergency department were considered to have hyperglycemia and were shifted to the Paediatric intensive care unit or the paediatric wards for further management. Data was collected as per the proforma. The blood sugar values were followed up in these children until restoration of normoglycemia. All the children were followed up till discharge or death in case of mortality. Associated risk factors were analysed between the survivors and nonsurvivors. Results: Among 102 children included in the study group from1 month to 12 yrs, 55 were infants, 37 in the age group of 1-5 yrs and 10 were more than 5 yrs. 60 were males and 42 were females. Family history of diabetes was encountered in 10 children. Out of 102 children, 60 recovered to hospital discharge. Sepsis, seizures, bronchopneumonia and CNS infections were the common illness among children with stress hyperglycemia. Age less than 1year, breathlessness, fever, shock, seizures and altered sensorium were identified to be significantly associated with mortality in children with stress hyperglycemia by univariate analysis in this study. Regression analysis revealed age less than one year, presence of lung infiltrates, longer duration of hyperglycemia, and need for Paediatric Intensive Care Unit (PICU) admission to be significantly associated with mortality. Non survivors had persistent hyperglycemia up to 48 hours in comparison to survivors. Overall mortality in the study group was 41%. Conclusions:Incidence of stress hyperglycemia is high in infants. Infections were the common underlying diagnosis in stress hyperglycemia. Being an infant, prolonged hyperglycemia for 48 hrs and need for PICU care were significantly associated with mortality. Overall mortality in children with stress hyperglycemia is 41%.